Dual beta-lactam treatment: Pros and cons. Issue 5 (24th September 2022) - Guerra, Diogo; Vidal, Pauline; Paccoud, Olivier; Maillard, Alexis; Cachera, Laurene; Junot, Helga; Gauzit, Rémy; Zahar, Jean R.; Abreu, Miguel A.; Bleibtreu, Alexandre
Abstract: The battle against microscopic pathogens has always baffled the scientific community. Nowadays, multidrug-resistant microorganisms lead to high in-hospital mortality, increased hospital stays, and high health-related costs. Treating infections due to these high-resistance pathogens with a low number of antibiotic molecules creates the need for new strategies. Although some already think of a "postantibiotic era" with bacteriophages as the main futuristic weapon in antibacterial armament, others rethink the usage of the already existent drugs. Dual beta-lactam therapy has been used for quite some time as an empirical therapy for some severe infections such as endocarditis or meningitis. However, studies regarding the use of a beta-lactam combination stopped being made a long time ago, and it seems the scientific community has no interest in evaluating this as a treatment option. Could this strategy be applied to treat infections due to multidrug-resistant bacteria? Could this be the answer while waiting for the "postantibiotic era"? What kind of pathogens could we fight using dual beta-lactams? What are the downsides of this strategy? These are some of the questions the authors try to answer in this review. In addition, we try to convince our peers to turn once more into researching beta-lactam combinations and exploring its potential benefits.